Pro-106-Ser mutation and EPSPS overexpression acting together simultaneously in glyphosate-resistant goosegrass (Eleusine indica) - Javid Gherekhloo (Nature Portfolio, 2017)
Abstract Glyphosate has been used for more than 15 years for weed management in citrus groves in the Gulf of Mexico, at up to 3–4 applications per year. Goosegrass (Eleusine indica (L.) Gaertn.) control has sometimes failed. In this research, the mechanisms governing three goosegrass biotypes (Ein-Or from an orange grove, and Ein-Pl1 and Ein-Pl2 from Persian lime groves) with suspected resistance to glyphosate were characterized and compared to a susceptible biotype (Ein-S). Dose-response and shikimate accumulation assays confirmed resistance of the resistant (R) biotypes. There were no differences in glyphosate absorption, but the R biotypes retained up to 62–78% of the herbicide in the treated leaf at 96 h after treatment (HAT), in comparison to the Ein-S biotype (36%). The 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) activity in the Ein-Or and Ein-S biotypes was over 100-fold lower than the Ein-Pl1 and Ein-Pl2 ones. The latter showed a high EPSPS-basal activity, a mutation at Pro-106-Ser position in the EPSPS gene, and EPSPS overexpression. The EPSPS basal and EPSPS overexpression were positively correlated. The R goosegrass biotypes displayed poor glyphosate translocation. Furthermore, this grassweed showed, for the first time, two mechanisms at the target-site level (Pro-106-Ser mutation + EPSPS overexpression) acting together simultaneously against glyphosate.